Elevated serum B-cell activator factor levels predict rapid progressive interstitial lung disease in anti-melanoma differentiation associated protein 5 antibody positive dermatomyositis - Yumeng Shi; Hanxiao You; Chang Liu; Yulu Qiu; Chengyin Lv; Yujing Zhu; Lingxiao Xu; Fang Wang; Miaojia Zhang; Wenfeng Tan (Orphanet Journal of Rare Diseases, 2024)
Abstract Background Rapid progressive interstitial lung disease (RP-ILD) is the leading cause of anti-melanoma differentiation associated protein 5 antibody positive dermatomyositis (anti-MDA5+DM) related death. Elevated serum B-cell activating factor (BAFF) levels have been implicated in connective tissue diseases associated ILD. Here, we evaluate whether BAFF could be a prognostic biomarker for predicting RP-ILD in anti-MDA5+DM patients. Methods Serums were collected from 39 patients with anti-MDA5+DM (20 with RP-ILD and 19 with non-RP-ILD), 20 antisynthase syndrome (ASS) patients and 20 healthy controls (HC). BAFF concentration was measured by an enzyme-linked immunosorbent assay. Results Serum BAFF level was higher in anti-MDA5+DM patients than those in ASS patients and HC (3882.32 ± 1880.09 vs. 2540.89 ± 1403.04 and 2486.28 ± 767.97 pg/mL, p = 0.0056 and 0.0038, respectively). Within anti-MDA5+DM groups, RP-ILD patients exhibited higher BAFF concentration than non-RP-ILD group (4549.78 ± 1839.97 vs. 3297.28 ± 1794.69 pg/mL, p = 0.04). The BAFF concentration was positively correlated with levels of C-reactive protein (CRP), dehydrogenase (LDH) and cytokeratin (CK) in anti-MDA5+DM patients (r = 0.350, p = 0.035; r = 0.393, p = 0.016; r = 0.518, p = 0.001; respectively). The best cut-off value of BAFF concentration was 2971.5 pg/mL by ROC curve (AUC area = 0.690, p = 0.045) and BAFF > 2971.5 pg/mL was an independent risk factor for RP-ILD using multivariate analysis (OR = 9.389, 95% CI = 1.609—54.769; p = 0.013). Conclusions Serum BAFF could be a useful prognostic biomarker for early detecting RP-ILD risk in anti-MDA5+DM patients.